Internal hiring or external recruitment? - Jed DeVaro (IZA World of Labor, 2020)
When an employer fills a vacancy with one of its own workers (through promotion or horizontal transfer), it forgoes the opportunity to fill the position with a new hire from outside the firm. Although firms use both internal and external hiring methods, they frequently favor insiders. Internal and external hires differ in observable characteristics (such as skill levels), as do the employers making the hiring decisions. Understanding those differences helps employers design and manage hiring policies that are appropriate for their organizations.
Keywords: M51; 330; internal promotion; external recruitment; lateral transfers; hiring